Prospects of cultural interaction between Russia and China in the field of higher education in the XXI century - V. M. Sotnikova (Вестник Майкопского государственного технологического университета, 2024)
The article examines the main problems of current Russian-Chinese relations in the field of cultural exchanges and higher education in Russia and China. The goal of the research is to identify the historical origins of the formation of cooperation between the two countries in the field of higher education, the possibilities of developing the system of intercultural communications in the education sector of Russia and China in modern conditions. The research methodology includes an analysis of cultural, historical, regional and social components. The main directions of merging the cultural areas of these countries have been compared. The cooperation between the Russian Federation and the People's Republic of China at the present stage and the prospects for its development in the field of education have been studied in detail. Close attention is aimed at improving the educational process and the development of intercultural relations. This cooperation has been considered on the example of several universities in Russia and China. The experience of organizing partnerships between universities has been studied through the prism of modern Russian educational practice. Further development prospects have been highlighted, taking into account their needs. As a result of the research, the author has concluded that, despite the constant changes in the modern geopolitical situation in the world, the relations between the countries remain stably diplomatic. It has been noted that the main priority of the Russian foreign policy towards China is the development of diplomacy and mutual communication between the two bordering states; options for solving the tasks set, linking them with Russia's change in its foreign policy course and directing it towards cooperation with China, the leader of East Asian countries have been proposed. These conclusions determine the desire of modern society to achieve mutual understanding in the field of intercultural communications between Russia and China.